Confiabilidade intra e inter-examinadores de uma escala de análise de movimento do pé durante a fase de apoio da marcha de indivíduos adultos jovens saudáveis - Guilherme Augusto Santos Araujo (2023)
The pronation and supination during the stance phase allow the foot to interact with the ground differently during the sub-phases of gait. Changes in magnitude, duration, and timing of these movements may be associated with the development and occurrence of different health conditions, such as hip pain, Achilles tendinopathy, and medial tibial stress syndrome. Thus, the clinical identification of changes in the foot movement pattern during the stance phase of gait assists the physiotherapist in verifying the need to assess musculoskeletal parameters related to changes in foot movement. This study aimed to develop a new scale for analyzing foot movements during gait (Foot Dynamic Index [PDI]) and investigate its intra- and inter-examiner reliability. The PDI was developed by a group of research physiotherapists with more than 10 years of experience in assessing foot movements during gait in clinical settings. Forty-nine healthy young adults (28 women and 21 men) participated in the study. Participants had a mean age of 23.72 ± 4.2 years, mean height of 1.69 ± 0.10 m, mean weight of 63.92 ± 11.28 kg, and mean body mass index of 22.37 ± 3.07 kg/m2. Intra-examiner reliability ranged from moderate to substantial (Kappa between 0.54 and 0.80), while inter-examiner reliability ranged from fair to substantial (Kappa between 0.28 and 0.68). These results suggest that the same clinician can use the PDI to assess foot movements at different times and with substantial reliability. Nevertheless, the comparison of results using the PDI by different examiners must be conducted with caution, mainly during the mid-stance of the gait.